2009
DOI: 10.4172/1948-5948.1000008
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Submerged Culture Conditions for Exo-Polysaccharides Production by Streptomyces Nasri-UV 135 in Bioreactor

Abstract: Production of Exopolysaccharides "EPS" and microbial biomass by Streptomyces nasri were influenced by the type of carbon source (glycerol, xylose, fructose, galactose, glucose, mannose, sucrose, lactose, maltose, dextrin, soluble starch, corn starch and potato starch) and the nitrogen source (glycine, aspartic acid, glutamic acid, proline, ammonium sulphate, sodium nitrate and beef extract ) used in the medium.Xylose and glycine were the most suitable sources of carbon and nitrogen, respectively, for both prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…During the past several decades, much interest has been generated in the subject of polysaccharides produced by microorganisms, due to their various biological and pharmacological activities, including immuno-stimulating and anti-tumour activities [54]. Polysaccharides are polymeric carbohydrate structures, formed of repeating units (either mono-or di saccharides) joined together by glycosidic bonds.…”
Section: Production Of Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past several decades, much interest has been generated in the subject of polysaccharides produced by microorganisms, due to their various biological and pharmacological activities, including immuno-stimulating and anti-tumour activities [54]. Polysaccharides are polymeric carbohydrate structures, formed of repeating units (either mono-or di saccharides) joined together by glycosidic bonds.…”
Section: Production Of Polysaccharidesmentioning
confidence: 99%
“…They prevent syneresis, and ensure proper texture and body of the end product. Further, it has been reported that EPS isolated from lactic acid bacterial cultures have antitumor activity [59,60]. These lactic acid bacteria also play an important role in the biodegradation of azo dyes [61].…”
Section: Exopolysaccharidesmentioning
confidence: 99%
“…In the 1980s, a glucoseutilizing mutant of Cupriadivus necator was employed by Imperial Chemical Industries (UK) for the industrial production of PHA which was sold under the trade name of Biopol TM [32]. Industrial production procedures considered various factors [33] for the efficient production of PHA. The factors include culture conditions, type of media required (which usually include complex mixtures of amino acids, vitamins, proteins, lipids, carbohydrates, nucleotides, nucleosides and minerals) [9,34], suitable microbe to be used, type of fermentation process, downstream techniques to get the purified raw form of PHA Bioplastics.…”
Section: Pha Productionmentioning
confidence: 99%